Electrical transport in carbon nanotube fibres. (1st April 2017) - Lekawa-Raus, Agnieszka; Gizewski, Tomasz; Patmore, Jeff; Kurzepa, Lukasz; Koziol, Krzysztof K.
Abstract: Individual carbon nanotubes are highly interesting electrical conductors which could well complete with superconductors. Yet, the possibility of production of top-performance carbon nanotube electrical conductors beyond nanoscale, is the question currently challenging scientists. This study discusses theoretical potential of macroscopic fibres made purely of carbon nanotubes, in charge transport and electrical applications. It also examines various aspects of their electrical conductivity including both direct and alternating current transport, weight-conductivity ratios, current density and doping issues. The reasons for the constraints in electrical transport in fibres manufactured today are explained, as are possible routes to achieving significant improvements in the performance. Graphical abstract: